BENTUK DEIKSIS TEMPAT DALAM IKLAN BELANJA ONLINE - Dicki Yustika Nurleli; Laili Etika Rahmawati (Linguistik : Jurnal Bahasa dan Sastra, 2020)
Advertising in online shopping serves as a means to promote or advertise a item or service in the hope that it increases the maximum income of the advertised product. Usually an ad uses very short, solid, clear and interesting languages to influence the community and public attention. This study aims to describe the form of deixis place online shopping ads. The method used in this study, namely qualitative descriptive method. Data in this study, in the form of clauses, sentences, and discourse containing deixis in online shopping ads. The data collection technique used is special and recorded techniques. Data analysis, including (1) grouping online shopping advertising data; (2) classifying Deiksis place form data; and (3) set aside similar data but is not the same based on the form of clauses, sentences, and discourses. The results of this study indicate that the form of deixis place online shopping advertisements with data from 13 data in the form of clauses, sentences, and discourses.